PENGARUH HARGA DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE: STUDI KASUS PADA HARAPAN MAULINA HIJAB JOMBANG - Ratna Dwi Jayanti (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2015)
In digital era now, the use of internet in the business has entered all lines of business included in the marketing of goods or services. Online sales or which is known as E-commerce, also used by Maulina Hijab Jombang. This research aims to analyze deeper the Influence of Price (X1) and Trust (X2) toward Online purchasing Decision. Type of research is explanatory involving 90 respondents. The analytical methods used were multiple linear regression, t- test and F- test. The result showed that the price factor (X1) is not dominant influenced on online purchase decisions on Maulina Hijab Jombang. While the “trust” factor (X2) the dominant influenced. This shows that consumers Maulina Hijab already believe that the quality of the goods sold is equivalent to the price offered.